The First Amendment v. reproductive rights: Crisis pregnancy centers, commercial speech, and marketplaces of misinformation. Issue 1 (2nd January 2020) - Queen, Bradley
ABSTRACT: This essay responds to the holding in National Institute of Family and Life Advocates (NIFLA) v. Becerra (2018), arguing that the signal contribution of the majority opinion is its attempt to move commercial speech further into the absolute realm of protected public discourse. In finding the California FACT Act to be unconstitutional, the 5–4 majority uses a fractured commercial speech standard to define NIFLA's marketplace communications as protected ideological speech. In so doing, Justice Thomas, author of the majority opinion, considers only the state's speech – its compelled disclosures – and does not assess the rhetorical properties of NIFLA's commercial communications. But the majority concludes nevertheless that NIFLA's speech is impervious to publicly interested legislation, despite well-documented evidence of misleading and harmful advertising. Ultimately, it is argued that the question of whether NIFLA's right to free speech has been violated cannot be squarely addressed if the speech with which the state's disclosures dialogue remains nebulous. NIFLA seems to undermine the longstanding conception of commercial speech as a form that legitimates both the interests of speakers and the informational interests of publics, with the latter sustained when necessary by governmental initiatives that enable informed choice-making by regulating deceptive information in commercial marketplaces.